Effect of HF Concentration on Physical and Electronic Properties of Electrochemically Formed Nanoporous Silicon. (24th February 2009) - Kumar, Pushpendra; Lemmens, Peter; Ghosh, Manash; Ludwig, Frank; Schilling, Meinhard
Abstract : The most common fabrication technique of porous silicon (PS) is electrochemical etching of a crystalline silicon wafer in a hydrofluoric (HF) acid-based solution. The electrochemical process allows for precise control of the properties of PS such as thickness of the porous layer, porosity, and average pore diameter. The effect of HF concentration in the used electrolyte on physical and electronic properties of PS was studied by visual color observation, measuring nitrogen sorption isotherm, field emission type scanning electron microscopy, Raman spectroscopy, and photoluminescence spectroscopy. It was found that with decrease in HF concentration, the pore diameter increased. The PS sample with large pore diameter, that is, smaller nanocrystalline size of Si between the pores, was found to lead to a pronounced photoluminescence peak. The systematic rise of photoluminescence peak with increase of pore diameter and porosity of PS was attributed to quantum confinement. The changes in nanocrystalline porous silicon were also clearly observed by an asymmetric broadening and shift of the optical silicon phonons in Raman spectra. The change in electronic properties of PS with pore diameter suggests possibilities of use of PS material as a template for fundamental physics as well as an optical material for technological applications.